Desaturase Activities in Rat Model of Insulin Resistance Induced by a Sucrose-Rich Diet - Brenner, Rodolfo Roberto (2003)
A sucrose-rich diet, as compared with a similar starch diet, induces a time-dependent typical noninsulin-dependent diabetes syndrome characterized by insulin resistance in rats. Within the first 3 wk, there was glucose intolerance associated with hyperinsulinemia, hypertriglyceridemia, and high plasma FFA. In this study, we examined the effect of the sucrose-rich diet vs. the starch diet during short-(3 wk) and long-term treatment (6 mon) on hepatic Δ9, Δ6, and Δ5 desaturases. These enzymes modulate monounsaturated FA and PUFA biosynthesis, respectively. Sucrose feeding (3 wk) caused an initial hyperinsulinemia that was normalized within 6 mon. In the early period (3 wk), stearoyl-CoA desaturase-1 (SCD-1) mRNA and activity were decreased, whereas Δ6 desaturase mRNA abundance and Δ6 and Δ5 desaturase activities remained unchanged. After 6 mon of sucrose feeding, activities of the Δ9, Δ6, and Δ5 desaturases were each increased. The SCD-1 and Δ6 desaturase mRNA were also correspondingly higher. These increases were consistent with an increase in oleic acid, the 20∶4/18∶2 ratio, and 22∶4n−6 and 22∶5n−6 acids in liver and muscle lipids. On the other hand, the percentage of 22∶6n−3 acid was decreased. In conclusion, a sucrose-rich diet after 6 mon induces an increase in rat liver SCD-1 and Δ6 desaturase mRNA and enzymatic activities that are opposite to the changes reported in insulin-dependent diabetes mellitus. It appears that neither blood insulin levels nor insulin resistance is a factor affecting the Δ9, Δ6, and Δ5 desaturase changes in mRNA and activity found with the sucrose-rich diet.